ANALISIS YURIDIS PENUNDAAN LELANG EKSEKUSI OLEH PENGADILAN NEGERI MEDAN TERHADAP HARTA BERSAMA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG RI No.601 PK/Pdt/2007) - PUDJI INDAH LESTARI (PREMISE LAW JURNAL, 2017)
ABSTRACT In the implementation of auction, there is auctioning organizational structure which in the central government it is known as Auction Administration Inspection, and the regional level the implementation and/or the Ruling on Auction Postponement from the Court should be informed in 3 (three) days prior to auctioning implementation. From the Articles found in the Civil Code and the Compilation of the Islamic laws, it is found that those who want to make an agreement, especially loan agreement, either in Sharia Banks or in Conventional Banks, have to fulfill the basic requirements stipulated in the Civil Code. The research problems were as follows: first, how about the legal force on foreclosure sale executed by the State Loan Service Office against non-performing loan; secondly, how about the legal provisions on joint property which is auctioned; thirdly, how about the postponement of foreclosure sale by the Medan District Court in its Ruling No. 601PK/Pdt./2007. The conclusion of the research is that legal force on foreclosure sale by the State Loan Service Office against non-performing loan in the execution or the implementation of the rulings is done by coercion on the loser in litigation. Article 35 of Law No. 1/1974 regulates joint property. In general, joint property is the property which is obtained during the marriage period in which both husband and wife attempt to fulfill their needs in their wedlock. The use of joint property needs formal or firm agreement. Keywords: Postponement of Foreclosure Sale, Medan District Court, Joint Property